2003
DOI: 10.1590/s0103-64402003000300009
|View full text |Cite
|
Sign up to set email alerts
|

Control of microorganisms in vitro by endodontic irrigants

Abstract: The aim of this study was to determine the minimum inhibitory concentration (MIC) and antimicrobial effectiveness by the direct exposure test of 4 endodontic irrigants [1% sodium hypochlorite (NaOCl), 2% chlorhexidine (CHX), 1% calcium hydroxide (Ca(OH) 2; prepared with 1 g of Ca(OH) 2 and 100 mL of sterile distilled water), a solution of Ca(OH) 2 + detergent (HCT20)] for S. aureus, E. faecalis, P. aeruginosa, B. subtilis, C. albicans and a mixed culture. Microbial growth was analyzed by two methods: turbidity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
69
2
7

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(79 citation statements)
references
References 16 publications
1
69
2
7
Order By: Relevance
“…This fact reinforces the concept of eliminating empty spaces that can harbor microorganisms (8,9,23,24). The RCT excellency is associated with the disinfection process, which involves removing microorganisms from the root canal system by emptying, cleaning and enlarging/shaping, combined with the use of antibacterial therapies (8,9,16,23,25,26). Based on the need to control the microbiota of infected root canals, some aspects are necessary in a therapeutic protocol.…”
Section: Operational Strategies That May Interfere On Successmentioning
confidence: 75%
See 3 more Smart Citations
“…This fact reinforces the concept of eliminating empty spaces that can harbor microorganisms (8,9,23,24). The RCT excellency is associated with the disinfection process, which involves removing microorganisms from the root canal system by emptying, cleaning and enlarging/shaping, combined with the use of antibacterial therapies (8,9,16,23,25,26). Based on the need to control the microbiota of infected root canals, some aspects are necessary in a therapeutic protocol.…”
Section: Operational Strategies That May Interfere On Successmentioning
confidence: 75%
“…The antimicrobial effect of sodium hypochlorite by direct contact with E. faecalis occurs after 2 min (25). The positive culture of microorganisms following the application of the irrigating solutions (ozonated water, gaseous ozone, 2.5% sodium hypochlorite, 2% chlorhexidine) for 20 min confirmed their inability to sterilize an infected human root canal (24).…”
Section: Sanitization Processmentioning
confidence: 92%
See 2 more Smart Citations
“…Vianna et al (3) and Estrela et al (4,5) showed that sodium hypochlorite is more bactericidal than chlorhexidine gel. In terms of tissue dissolution, efficiency is proportional to hypochlorite concentration in the solution (6,7).…”
Section: Introductionmentioning
confidence: 99%